Stromal depletion by TALEN-edited universal hypoimmunogenic FAP-CAR T cells enables infiltration and anti-tumor cytotoxicity of tumor antigen-targeted CAR-T immunotherapy - Das, Shipra; Valton, Julien; Duchateau, Philippe; Poirot, Laurent (Frontiers in Immunology, 2023)
Adoptive cell therapy based on chimeric antigen receptor (CAR)-engineered T-cells has proven to be lifesaving for many cancer patients. However, its therapeutic efficacy has so far been restricted to only a few malignancies, with solid tumors proving to be especially recalcitrant to efficient therapy. Poor intra-tumor infiltration by T cells and T cell dysfunction due to a desmoplastic, immunosuppressive microenvironment are key barriers for CAR T-cell success against solid tumors. Cancer-associated fibroblasts (CAFs) are critical components of the tumor stroma, evolving specifically within the tumor microenvironment (TME) in response to tumor cell cues. The CAF secretome is a significant contributor to the extracellular matrix and a plethora of cytokines and growth factors that induce immune suppression. Together they form a physical and chemical barrier which induces a T cell-excluding ‘cold’ TME. CAF depletion in stroma rich solid tumors can thus provide an opportunity to convert immune evasive tumors susceptible to tumor-antigen CAR T-cell cytotoxicity. Using our TALEN-based gene editing platform we engineered non-alloreactive, immune evasive CAR T-cells (termed UCAR T-cells) targeting the unique CAF marker Fibroblast Activation Protein, alpha (FAP). In an orthotopic mouse model of triple-negative breast cancer (TNBC) composed of patient derived-CAFs and tumor cells, we demonstrate the efficacy of our engineered FAP UCAR T-cells in CAF depletion, reduction of desmoplasia and successful tumor infiltration. Furthermore, while previously resistant, pre-treatment with FAP UCAR T-cells now sensitized these tumors to Mesothelin (Meso) UCAR T-cell infiltration and anti-tumor cytotoxicity. Combination therapy of FAP UCAR, Meso UCAR T cells and the checkpoint inhibitor anti-PD-1 significantly reduced tumor burden and prolonged mice survival. Our study thus proposes a novel treatment paradigm for successful CAR T-cell immunotherapy against stroma-rich solid tumors.